2021
DOI: 10.3390/s21196387
|View full text |Cite
|
Sign up to set email alerts
|

Face with Mask Detection in Thermal Images Using Deep Neural Networks

Abstract: As the interest in facial detection grows, especially during a pandemic, solutions are sought that will be effective and bring more benefits. This is the case with the use of thermal imaging, which is resistant to environmental factors and makes it possible, for example, to determine the temperature based on the detected face, which brings new perspectives and opportunities to use such an approach for health control purposes. The goal of this work is to analyze the effectiveness of deep-learning-based face det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It is because certain experiments allow their subjects to freely move their head and body in any direction as long as the subject's head positions can still be captured by a thermal camera. The global facial tracking method is noticeable in the studies proposed in [2], [18], with the use the DL-based object tracking method to track the entire face image with or without wearing a protective face mask with nearly 99% correctly as compared to local facial tracking that may use nose area in studies described in [3], [32]- [34]. It differs from previous studies in [35], which deliberately included the nose and mouth regions because the airflow mainly gets in and out of those regions.…”
Section: ) Facial Tracking Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because certain experiments allow their subjects to freely move their head and body in any direction as long as the subject's head positions can still be captured by a thermal camera. The global facial tracking method is noticeable in the studies proposed in [2], [18], with the use the DL-based object tracking method to track the entire face image with or without wearing a protective face mask with nearly 99% correctly as compared to local facial tracking that may use nose area in studies described in [3], [32]- [34]. It differs from previous studies in [35], which deliberately included the nose and mouth regions because the airflow mainly gets in and out of those regions.…”
Section: ) Facial Tracking Methodsmentioning
confidence: 99%
“…Recent studies have shown insufficient evidence to support the implementation of extractor methods to solve the problems with subjects wearing glasses or protective face masks during the experiments. This could explain why several researchers have purposefully included their subjects wearing glasses or protective face masks to evaluate the preciseness of their purposed methods [18], [19].…”
Section: A Data Preprocessingmentioning
confidence: 99%
“…In [196] Another notable group of works [29,197,198] focused on the collection of datasets for COVID-19 related applications using thermal imaging. Queiroz et al [29], for example, utilized a large-scale multimodal dataset known as SpeakingFaces [208] that consists of thermal images as well as visual and audio streams.…”
Section: Datasetsmentioning
confidence: 99%
“…There have been several previous studies regarding thermal camera sensors and LoRa. Thermal camera sensors are used for tracking and facial recognition because there is abuse in facial manipulation by using excessive makeup and using masks that are not following the rules [22] [23]. In addition, a thermal camera sensor is used to find out the whereabouts of a person somewhere [24].…”
Section: Introductionmentioning
confidence: 99%